(3KeQI GdEQTGO hJeRjL GdCQhGM hGdCLSGOs - (3Ydj LdHi GdLdOci (B((3Ydj Hc GdGRfHbi(B) (3GdTgjQ HGdMcje GdLOjO hHGdeDda GdLOjO,J (B1018 (3g` s
(3ChdgG (B:s
(3hHYO, CYGffG Gddg hEjGc Ydi QYGjI hOGFYg hMaX eG GhOYfG ef UfGFYg s
(3BNQgG (B:s
(3Ef NQL eGDgG CUaQ e JSQb GdOGQ gi ajg hcd ef QBg gGHg JeJ GdCTLGQ hGdejGg hGdeYGOf hGdNQR HMeO Gddg s
(3GdfSNI ecedI HNW eNGda ddfSNI HYHGQI NJGe eaJYdI MJi JHOh GdfSNI cGedIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B53s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B667 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B29 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdcjejGA h GdWHjYjGJs